PEMBELAJARAN MENULIS TEKS DESKRIPSI DENGAN MENGGUNAKAN METODE DISCOVERY LEARNING PADA SISWA KELAS X - Riska Juliyanti; Lilih Suryani (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2018)
This study aims to describe: (1) learning to write text description by using discovery learning in grade X SMK students, (2) ability of student of class X of SMK in writing description text by using discovery learning method. This lesson plan with qualitative descriptive research. The subject of this research is teachers and students of class X SMK. The object of this research is to learn to write description text with discovery leraning method. This method to collect data is the method of observation and test method. The collected data were analyzed by qualitative descriptive and descriptive quantitative analysis method. The results show that (1) learning to write description text using discovery learning method by teacher in accordance with existing plan. (2) the ability in class X of SMK in writing description text is good. The scores obtained are 78.13. Although a good score is achieved after achieving success, teacher performance improvements must be improved by providing better practice questions, to achieve maximum results.